Factors influencing international students’ choice of educational destination: A systematic review through the socioecological model lens - Hemati, Marziye; Pourasghari, Hamid; Meshkani, Zahra; Motamed-Jahromi, Mohadeseh (Journal of International Students, 2026)
International student recruitment is a key trend in global higher education and has consistently been a major focus for universities worldwide. This study aims to identify the factors influencing decision-making for educational destinations through a socio-ecological approach, offering policymakers actionable insights to effectively attract international students. It was a systematic review. English-language articles published between 2019 and 2024 were selected from five databases. A total of 29 articles were included. Thematic analysis revealed ten themes influencing international student decision-making, categorized into individual, interpersonal, organizational, sociocultural, and public policy factors, in alignment with the levels of the socio-ecological model.